The ‘Art’ of Science and Research: Jabir Ibn Hayyan Laid the Foundation - Syed, Naweed I; Syed, Areej Zehra; Naqvi, Syed Rehan (International Journal of Endorsing Health Science Research, 2021)
This article identifies scientists' attributes and their approaches to innovation, sciences, research, and discovery as ascribed by Abu Musa-Jabir Ibn Hayyan al- Azdi - also known as Jabir Ibn Hayyan (or Geber) in the late 7th to early 8th century. Jabir was the first polymath to have set the stage for the Golden Age of Islam that lasted from the 8th to 12th century. In several of his books and research articles, Jabir identified researchers, scientists and scholars as the “artists” and their research methodologies and experimentation as the "art." A mastery or specialization in any given discipline that an "artist' pursues was termed by him as the “Majistery”. The attributes that he proposed several centuries ago have since become the criteria, befitting the “art” of our present-day scientists and scholars. He explicitly detailed the attributes of an “artist” and also those who were recommended not to pursue sciences as a career. He described natural talent, innate propensity, the conquest of knowledge, deeper insights into Mother Nature, ingenuity, critical thinking, foresight, flexibility, adaptability, resiliency, persistence and selflessness as the essential ingredients of scientists and their success. Additionally, he also deemed funding, collaboration, partnership and community support to be pivotal. Rigidity – the "stiff neck," as he described it, and the lack of adaptability to be detriments to the ‘art’ of sciences. This article provides an eye-opening account of the scientific rigor that led to the Golden Age on the one hand, and on the other hand, attempts to reconcile the compatibility of modern sciences with traditional Islamic teachings. It also identifies the critical success factors that led to the rise of sciences in the Islamic world, which have since either been forgotten or ignored. We make recommendations throughout as to what needs to be done to revive the Golden Age of Sciences in the Muslim world.